تطبيق حفظ المفردات العربية لتنمية مهارة الكلام لطلاب المعهد الإسلامي " منبع الصالحين" سوجي غرسيك - رفكي ذو الفهم, محمد (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2024)
Vocabulary is one of the elements of the language that learners of foreign languages, including Arabic, must possess. Sufficient Arabic vocabulary can support someone in communicating and writing in that language. School students are often taught new words as part of certain subjects and many adults also consider vocabulary building an interesting learning activity. The research questions for this research are: (1) How to teach speaking skills to students at the Source of the Righteous Institute? (2) How is vocabulary memorization applied to develop speaking skills for students of the Islamic Institute “The Source of the Righteous” Suji Gresik?This research used qualitative research methods. This method is how. The results of the research are as follows: Teaching speech skills to students at the Manba’at al-Saliheen Institute in a manner and its steps: As for the steps of the Arabic Language Department for teaching vocabulary at Dar Maba’at al-Shahatin. Supervisors will provide the vocabulary words that will be pasted on the bulletin board in each complex. 2. Students must write the vocabulary words when they are pasted3. Arabic language supervisors will read the vocabulary over the loudspeaker at the home. 4. Supervisors want to ask students who go to school. 5. Students will be given an opportunity to give a speech. The application of vocabulary memorization to develop students’ speaking skills is done through the use of vocabulary exercises over loudspeakers in the morning sessions, and the second is to paste the vocabulary in a specific place in each complex, such as a bulletin board, and thus the vocabulary is applied to develop the students’ speaking skill when memorizing it, and of course there will be continuity. The new vocabulary continues with the previous vocabulary.